Contextual Meaning and Its Impact on the Evolution of Meaning - bouzid, bouzid (El Omda in Linguistics and Discourse Analysis, 2022)
Abstract: The context is a linguistic entity that appears in the set of lexical, phonetic and synthetic relations that describe the text with coherence, in terms of its internal structure and the position in which it is said. coherence of the linguistic unit; That is, placing them in multiple contexts and that most of the semantic units lie in the vicinity of other units, and the meanings of these units cannot be described or determined except by observing the units that are adjacent to them. Which requires connecting this to the meaning .